Violation of Cooperation Principle in the Discourse of Student WhatsApp Groups at Vocational High School PIKA Semarang - Sri Rahayu, M. Fransiska; Rustono, Rustono; Haryadi, Haryadi (Universitas Negeri Semarang, 2022)
This study describes the violation of the cooperative principle in the discourse of the 43rd batch students' WhatsApp group at Vocational High School PIKA Semarang. The theory used in this study is Grice's (1975) theory, which states that speakers must pay attention to four maxims of cooperative principles in communicating: quantity maxim, quality maxim, relevance maxim, and manner maxim. The study used a descriptive qualitative approach. The data collection method used is listening and recording. The research object is speech events that occur in the discourse of students' WhatsApp group at Vocational High School PIKA Semarang. The forms of violations found in this fragment the discourse of student WhatsApp group at Vocational High School PIKA Semarang, there are sixteen data, including three data in the form of a quantity maxim violation, three data in the form of a quality maxim violation, four data in the form of a relevance maxim violation, and six data in the form of a maxim violation. The reason for the violation of the maxim is to generate interest in the form of cuteness, superior quality, and even satireand imagery in poetry anthology Perahu Kertas by Sapardi Djoko Damono.